(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction: Spontaneous rupture of renal angiomyolipoma (AML) is a rare but life-threatening condition that can lead to severe hemorrhagic shock and acute kidney injury. AML is a benign mesenchymal tumor that is often asymptomatic but carries a risk of rupture, particularly in lesions larger than 4 cm or in patients with underlying conditions such as tuberous sclerosis complex. This case report highlights the intensive management of a patient with ruptured renal AML, emphasizing the importance of early diagnosis, multidisciplinary collaboration, and advanced diagnostic tools. Case presentation: A 37-year-old male with a history of bilateral AML was admitted due to spontaneous rupture of a large left renal AML, resulting in hemorrhagic shock (hemoglobin 1.9 g/dL), coagulopathy, and acute kidney injury. The patient required emergency intubation, aggressive resuscitation with blood products, and urgent left nephrectomy due to extensive tumor invasion. Postoperatively, the patient developed worsening acute kidney injury requiring continuous renal replacement therapy, along with hemostatic management guided by rotational thromboelastometry (ROTEM). Despite the critical initial condition, the patient stabilized after 72 hours of intensive care, with gradual recovery of renal function and no additional complications. Conclusion: This case highlights the challenges in managing ruptured AML, particularly in the setting of massive hemorrhage and acute kidney injury. It underscores the crucial role of early diagnosis, timely surgical intervention, and advanced diagnostic tools such as ROTEM in optimizing patient outcomes. A multidisciplinary approach, involving urologists and intensivists, is key to successful management.